Technologies in the theater: from craftsmanship to digital - Dos Santos Cunha, María José (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
In this article, we approach the technological revolution in the world of art, more specifically, in the theatre. The intended objectives were to analyse and reflect on how theatrical practices were, and are, enhanced when mediated by technology. The methodology used was a bibliographic search, and with the development of the work, it was possible to conclude that in an environment of drastic change, such as the one we live in currently, the theatre has to adapt, readjust and creatively respond to the new challenges of technology, so that an innovative theatre can result from that.